NINETY YEARS OF THE PALEONTOLOGICAL SOCIETY - Zhamoida A.I. (My University, 2006)
The establishment in 1916 and the subsequent 90-year history of the Russian (later All-Union and All-Russia) Paleontological Society are discussed. The society’s works and endeavors over ninety years were closely connected with the needs of practical geology, and primarily with paleontological research, the development of a stratigraphic basis, and their use in paleogeography, paleoecology, and biosphere studies.